2001
DOI: 10.1161/01.cir.103.22.2668
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Heart Failure Among Adult Patients With Diabetes

Abstract: These results confirm previous evidence that poor glycemic control may be associated with an increased risk of heart failure among adult patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
276
3
25

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 601 publications
(319 citation statements)
references
References 34 publications
(19 reference statements)
15
276
3
25
Order By: Relevance
“…Furthermore, it has been reported that poor glycemic control is associated with a higher rate of HF admissions [6]. For example, Iribarren et al [7], in a cohort of about 50,000 diabetic patients (none of whom had a reported history of HF), reported that each 1% increase in HbA1c correlated with an 8% increased risk of HF. Unfortunately, tightening the control of blood glucose did not appear to result in a decreased risk of HF [8].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that poor glycemic control is associated with a higher rate of HF admissions [6]. For example, Iribarren et al [7], in a cohort of about 50,000 diabetic patients (none of whom had a reported history of HF), reported that each 1% increase in HbA1c correlated with an 8% increased risk of HF. Unfortunately, tightening the control of blood glucose did not appear to result in a decreased risk of HF [8].…”
Section: Discussionmentioning
confidence: 99%
“…These include the accumulation of advanced glycation end products, altered calcium handling, increased reactive oxygen species (ROS) and activation of the renin-angiotensin system (Fiordaliso et al 2004, Ligeti et al 2006, Goh & Cooper 2008, Yao & Brownlee 2010, Thomas et al 2013. Indeed, a study of almost 50,000 individuals with diabetes demonstrated that, for each 1% increase in glycated haemoglobin, there was an 8% increase in the risk of heart failure (Iribarren et al 2001). Interestingly, this effect was observed independent of hypertension status, consistent with the finding that diabetic cardiomyopathy can occur in the absence of hypertension as mentioned previously (Rubler et al 1972, Regan et al 1977.…”
Section: Introductionmentioning
confidence: 99%
“…Prior data predictive of HF in asymptomatic diabetics are limited, particularly over a long period of observation [20,21]. In a recent echo-Doppler-based study in type 2 diabetics, measures of LV diastolic dysfunction correlated with CV outcomes but HF was not examined [19].…”
Section: Discussionmentioning
confidence: 99%